Quality Comparison of Flavoured and Non-flavoured Yoghurts from Animal and Vegetable Milk Sources - Ogbonna, Augustine Chima; Abuajah, Christian Izuchukwu; Ukeme, Edet Albert (Food Biology, 2013)
In this study, the physico-chemical, microbiological and organoleptic properties of flavoured and non-flavoured yoghurt samples made from powdered whole milk (PWM) and soymilk (SYM), were comparatively evaluated using standard methods. The results were significantly (p<0.01) different and showed that PWM yoghurt samples contained higher moisture (77.8 ± 0.025-78.21 ± 0.48%); lactose (1.02 ± 0.01-1.86 ±0.03%); crude fat (3.29 ± 0.10- 3.30 ±0.10%); TTA (total titratable acidity: 0.21 ±0.02- 0.25 ±0.01%) and pH (4.17 ±0.12-4.40±0.02) while SYM yoghurt samples recorded higher total solids (13.05 ± 2.01- 13.11 ±0.64%); ash (0.76 ± 0.02-0.79 ±0.04%); crude protein (3.35 ± 0.09 – 4.76 ±0.12%); crude fibre (0.81 ± 0.02 – 0.88 ± 0.01%) and specific gravity (0.82 ± 0.01-0.84 ±0.00). No lactose was detected in SYM yoghurt. There was significant (p<0.01) difference in the total microbial count of the two samples while some other non-identified growths were observed. Blind organoleptic evaluation results of the flavoured yoghurt samples showed significant (p<0.01) differences in the sensory attributes measured with PWM2 yoghurt being more generally acceptable than SYM2. However, no significant (p<0.01) effect of flavourings on general acceptability of the yoghurt samples was established.